Fixing Freddie : a true story about a boy, a mom, and a very, very bad beagle - Munier, Paula. (Adam Media, 2010)
In this memoir, single mother Paula Munier takes on the world's worst beagle--and loses every time. She tries everything to fix Freddie--but nothing really works. As her youngest son grows up and prepares to leave her soon-to-be empty nest, Paula's worst fear is that after more than thirty years of raising kids, she'll be left all alone--with Freddie.